Exploring the Contributions of Nepalese Mathematicians in the Modern Era with a Specific Emphasis on Research Areas - Raikhola, Sher Singh (Patan Prospective Journal, 2023)
This study explores the extensive realm of modern Mathematical research carried out by Nepalese Mathematicians, analyzing their substantial contributions across different Mathematical fields amid Nepal's changing socioeconomic context. Through comprehensive research, it elucidates the development of Mathematical concepts, the emergence of skilled Mathematicians, and the influence of their research on both local and international Mathematical communities. The paper aims to spotlight renowned Nepalese Mathematicians of the Modern era and their doctoral research endeavors, underscoring the pivotal role of Mathematics in shaping the country's path and progress.